Case Report: mRNA vaccination-mediated STAT3 overactivation with agranulocytosis and clonal T-LGL expansion - Hirsiger, Julia R.; Tzankov, Alexandar; Alborelli, Ilaria; Recher, Mike; Daikeler, Thomas; Parmentier, Stefani; Berger, Christoph T. (Frontiers in Immunology, 2023)
Vaccines against SARS-CoV-2 are the most effective measure against the COVID-19 pandemic. The safety profile of mRNA vaccines in patients with rare diseases has not been assessed systematically in the clinical trials, as these patients were typically excluded. This report describes the occurrence of agranulocytosis within days following the first dose of an mRNA-1273 vaccination against COVID-19 in a previously healthy older adult. The patient was diagnosed with a suspected STAT3 wild-type T-cell large granular lymphocytic leukaemia (T-LGL). Neutropenia was successfully treated with IVIG, glucocorticoids, and G-CSF. In vitro experiments aimed at elucidating the pathways potentially causing the mRNA vaccine-associated neutropenia indicated that the mRNA, but not the adenoviral Ad26.COV2.S vector vaccine, triggered strong IL-6/STAT3 activation in vitro, resulting in excessive T-cell activation and neutrophil degranulation in the patient but not in controls. mRNA-1273 activated TLR-3 suggesting TLR mediated IL-6/STAT3 pathway activation. To complete the primary series of COVID-19 immunization, we used a single dose of Ad26.COV2.S vector vaccine without reoccurrence of neutropenia. The T-LGL clone remained stable during the follow-up of more than 12 months without ongoing therapy. Our data suggest that switching the immunization platform may be a reasonable approach in subjects with rare associated hematologic side effects due to excess STAT3-mediated stimulation following mRNA vaccination. Using in vitro testing before re-administration of a (COVID) vaccine also has relevance for other rare immune events after (mRNA) vaccination.